Comprehensive Evaluation of Blast Casting Results Based on Unascertained Measurement and Intuitionistic Fuzzy Set - Li Ma; Jianguo Zhang; Chen Xu; Xingping Lai; Qiang Luo; Chendong Liu; Kemin Li (Shock and Vibration)
In order to make a scientific and accurate evaluation of blast casting results, according to the characteristics of blast casting-dragline stripping system, effective casting rate, looseness coefficient, limit vibration velocity, powder factor, fragmentation distribution, muck pile shape, boulder generation, damage degree of coal seam step, and dust pollution are selected as the evaluation indicators of blast casting results, and a classification standard is established. The unascertained measure theory was adopted to determine the membership degree of influencing factor indicator, which expanded the expression method of fuzzy information of evaluation indicators. The Analytic Hierarchy Process was used to determine the subjective weight of indicators, the entropy weight method was used to determine the objective weight of indicators, and the intuitionistic fuzzy set was used to express the range of the comprehensive weights of indicators. An evaluation model of blast casting results was constructed based on unascertained measurement and intuitionistic fuzzy set. The measured and processed data of blast casting in Heidaigou Open-Pit Coal Mine were calculated by the evaluation model. Besides, the sensitivity of indicator weights to the evaluation result of blast casting results was also analyzed. The results show that the blast casting results are level III (well). The effective casting rate ranks first in terms of the influence on the evaluation result, followed by damage degree of coal seam step, muck pile shape, looseness coefficient, powder factor, dust pollution, limit vibration velocity, and boulder generation/fragmentation distribution, and it was proved that the weight fluctuation of the evaluation indicator has no obvious correlation with weight.